Medicinal Plants as a Drug Alternative Source for the Antigout Therapy in Morocco - Nour Elhouda Daoudi; Mohamed Bouhrim; Hayat Ouassou; Mohamed Bnouham (Scientifica)
Background. The gout is a metabolic disease that is associated with a high level of uric acid in the blood. This disease is treated with some medications that aim to reduce serum urate levels. However, the use of various medicines leads to the appearance of some side effects, hence the importance of using other treatments based on natural resources. Objective. This study presents some medical treatments, their side effects, and some plants that are used for gout management in Morocco in the aim to valorize them. Methods. We have been consulting various English publications in PubMed, Web of Science, and ScienceDirect published between 1991 and 2019 using the following keywords “drugs,” “gout,” “Morocco,” “medicinal plants,” “in vitro,” and “in vivo” terms. Then, we have classified the medicines, according to their action mechanisms, and we have cited some species that were reported in Moroccan pharmacopeia as antigout. Results. Three methods of the gout medical management were cited in this work: xanthine oxidase inhibitors, uric acid excretion enhancer, and uricase recombinant. However, it was found that these treatments had various side effects. We have described 23 species, and some of them showed experimentally an antigout effect by blocking the “xanthine oxidase” enzyme. These plants belong to 11 families. Lamiaceae represents the most dominant family with six species followed by Asteraceae with two species. Colchicine isolated from Colchicum autumnale is the most known compound for its efficiency towards gout. Conclusion. This work summarized different treatments particularly medicinal plants that are used in Morocco to treat gout disease by blocking uric acid secretion. However, several studies are needed to valorize these antigout natural sources.